2006
DOI: 10.1016/j.desal.2005.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Control of residual aluminum from conventional treatment to improve reverse osmosis performance

Abstract: Soluble aluminum (Al 3+ ) may react with both ambient silica and antiscalant components to form colloidal foulants during reverse osmosis (RO) treatment. Whereas conventional treatment (coagulation/filtration/sedimentation/dual-media filtration) was being used prior to RO, aluminum sulfate (alum) and polyaluminum chloride (PACl) coagulants were evaluated at ambient pH (pH 7.8 to 7.9) and suppressed pH (pH 6.7) in an effort to lower the total aluminum to below 50 µg/L-a level previously observed to prevent RO m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(29 citation statements)
references
References 11 publications
2
26
0
1
Order By: Relevance
“…28% is observed and after 17 h of exposure and it has been suggested that aluminium can accumulate on the surface of membranes over time resulting in reduced flux [51]. A plot of the normalized absorbance ratio versus time for a sample of the membrane exposed to 25 ppm chloramine and 0.3 ppm Fe 2+ solution is shown in Figure 7(c).…”
Section: Structural Changes Measured By Infrared Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…28% is observed and after 17 h of exposure and it has been suggested that aluminium can accumulate on the surface of membranes over time resulting in reduced flux [51]. A plot of the normalized absorbance ratio versus time for a sample of the membrane exposed to 25 ppm chloramine and 0.3 ppm Fe 2+ solution is shown in Figure 7(c).…”
Section: Structural Changes Measured By Infrared Spectroscopymentioning
confidence: 99%
“…The images of the membranes exposed to Cu 2+ (Figure 3(c)) and the combination of Al 3+ /Fe 2+ (Figure 3(d)) show evidence of ubiquitous particles on the surface that varied in size and shape. The presence of these particles could potentially block some of the membrane pores resulting in changes in permeate conductivity and flux [51].…”
Section: Effect Of Chloramine On Membrane Surfacementioning
confidence: 99%
“…The active layer of the membrane was shown at 1656 cm -1 , indicating amide I group (C=O) [25], while the amide II group (N-H) that should be visible at 1540 cm -1 did not appear in the FTIR. Another band that could be characteristic of the polyamide group is C=C ring vibration at 1490 cm -1 [25].…”
Section: Membrane Fouling and Autopsymentioning
confidence: 95%
“…Poly-aluminium chloride is advantageous over monomeric flocculants as it i) is more thoroughly dispersed, ii) doesn't have an impact on the clarifier, iii) forms no insoluble residues and iv) achieves better turbidity removal than alum. However, it is less effective in improving the water colour than traditional flocculants [27,28].…”
Section: B Polymeric Coagulantsmentioning
confidence: 99%